Learning Ecosystems for Dealing with the Copy-Paste Syndrome - Kulathuramaiyer, Narayanan; Maurer, Hermann (Journal for Research in Innovative Teaching, 2008)
The fact that people of all walks of life are becoming more and more reliant on a wide-range of easily-available digital content is often called the Copy-Paste Syndrome. It implies the indiscriminate usage of material, ie without checking for reliability or a concern for violations of intellectual property rights or plagiarism, a kind of cheating that has become uncomfortably widespread. A holistic approach is required to address this universal problem combining an institutional approach together with the application of viable technologies, ...